Penerapan Teknologi Pembuatan Vidio Dalam Upaya Pemulihan Ekonomi UMKM Makanan, Fashion, Mebel Kecamatan Suruh, Kabupaten Semarang - Mellasanti ayuwardani; Bagus yunianto wibowo; Nanang adie setyawan; Vinda setya kartika; Hamsar suci amalia (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
Technological developments also affect the development of the economic and business world. From the problems of MSMEs and previous community service experiences, the community service team provided assistance and application of marketing video-making technology to 5 members of MSMEs KPM PKH Graduasi, Suruh District, Semarang Regency. In this service, the community service team also provided several equipment and tools to support the making of good marketing videos. The MSMEs that the team chose are MSMEs that sell products that can be videoed with the help of the facilities that will be provided. The five MSMEs consist of MSMEs with culinary businesses (cakes and chips), clothing resellers and handicraft businesses (furniture). In the video-making training, they directly use the products owned by MSMEs.